Phylogeography of Rhodiola kirilowii (Crassulaceae): a story of Miocene divergence and quaternary expansion. - Jian-Qiang Zhang; Shi-Yong Meng; Guang-Yuan Rao (PLoS ONE, 2014)
The evolution and current distribution of the Sino-Tibetan flora have been greatly affected by historical geological events, such as the uplift of the Qinghai-Tibetan Plateau (QTP), and Quaternary climatic oscillations. Rhodiola kirilowii, a perennial herb with its distribution ranging from the southeastern QTP and the Hengduan Mountains (HM) to adjacent northern China and central Asia, provides an excellent model to examine and disentangle the effect of both geological orogeny and climatic oscillation on the evolutionary history of species with such distribution patterns. We here conducted a phylogeographic study using sequences of two chloroplast fragments (trnL-F and trnS-G) and internal transcribed spacers in 29 populations of R. kirilowii. A total of 25 plastid haplotypes and 12 ITS ribotypes were found. Molecular clock estimation revealed deep divergence between the central Asian populations and other populations from the HM and northern China; this split occurred ca. 2.84 million year ago. The majority of populations from the mountains of northern China were dominated by a single haplotype or ribotype, while populations of the HM harbored both high genetic diversity and high haplotype diversity. This distribution pattern indicates that HM was either a diversification center or a refugium for R. kirilowii during the Quaternary climatic oscillations. The present distribution of this species on mountains in northern China may have resulted from a rapid glacial population expansion from the HM. This expansion was confirmed by the mismatch distribution analysis and negative Tajima's D and Fu's FS values, and was dated to ca. 168 thousand years ago. High genetic diversity and population differentiation in both plastid and ITS sequences were revealed; these imply restricted gene flow between populations. A distinct isolation-by-distance pattern was suggested by the Mantel test. Our results show that in old lineages, populations may harbour divergent genetic forms that are sufficient to maintain or even increase overall genetic diversity despite fragmentation and low within-population variation.